Critiques of Presentism in Criminology: challenges and Paradoxes - Catello, Roberto (Law, crime & history, 2023)
This article analyses recent critiques of presentism in criminology. Accusations of presentism in criminology are mainly of two kinds: those critiquing an insufficient interest in the study of criminology’s past and those critiquing an inadequate interest in the historical study of crime-related phenomena. The article identifies four general manifestations of presentism in contemporary criminology: presentism in criminology refers to i) a form of historical short-sightedness and a kind of harmful forgetfulness, ii) a way of burying the past, iii) a mode of being perpetually stuck in an eternal present, and iv) a failure to learn from the past. The article also discusses a variety of technical (i.e., historiographic) manifestations of criminological presentism that reveal some of the challenges and paradoxes inherent in the use of historical research in criminology.